Jayavardhanapura saṅgharāja parapura : Bu.Va. 1967-2043, Kri.Va. 1424-1500 - Rōhaṇadīra, Măndis, 1931- (Rōhaṇadīra, 1978)
Study of the Buddhist monastic hierarchy during the Kotte period of history of Sri Lanka.